Residential segregation and the integration of immigrants: Britain, the Netherlands and Sweden - Karen Schönwälder (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2007)
Three country studies on Great Britain (C. Peach), the Netherlands (S. Musterd/W. Ostendorf), and Sweden (R. Andersson) outline key features of ethnic residential segregation and discuss their relevance for the integration of migrants. For all three countries the degree of settlement concentration is considered moderate. Empirical results are presented on links between neighbourhood and, e. g., labour market integration and inter-group relations. In a concluding chapter, Karen Schönwälder offers an assessment of the available evidence on neighbourhood effects and its relevance for the German situation. While it seems too early to draw firm conclusions, current knowledge suggests that the importance of socio-spatial structures for the integration of people with a migration background should not be overestimated. The evidence does not support a choice of political intervention strategies that focus on countering ethnic residential segregation. – – Drei Länderstudien zu Großbritannien (C. Peach), den Niederlanden (S. Musterd/W. Ostendorf) und Schweden (R. Andersson) skizzieren Grundmuster der ethnischen residenziellen Segregation und diskutieren deren Relevanz für die Integration von MigrantInnen. Übereinstimmend schätzen sie den Grad der Siedlungskonzentration als moderat ein. Zur Bedeutung des Wohnumfeldes für u. a. die Arbeitsmarktintegration oder Gruppenbeziehungen werden einige empirische Ergebnisse vorgestellt. Karen Schönwälder bilanziert deren Aussagekraft und Relevanz für Deutschland. Obwohl sichere Einschätzungen noch nicht möglich sind, spricht der heutige Kenntnisstand dafür, die Bedeutung sozialräumlicher Strukturen für Integrationsprozesse von Menschen mit Migrationshintergrund nicht zu überschätzen und sie nicht in den Mittelpunkt politischer Steuerungsbestrebungen zu stellen.
Keywords: 300